The Anti-Cancer League and public outreach for cancer control in Peru - Raúl Necochea López (História, Ciências, Saúde: Manguinhos)
Abstract Peru’s first cancer control public outreach scheme started in the 1910s, but ground to a standstill as it attained official governmental recognition in 1926 as the Liga Anti-Cancerosa (LAC). This paper explains the developments leading to that earliest effort to enlist a coalition of State health agencies, physicians, and lay people in a campaign to publicize early signs of this disease, as well as the medical and political reasons for and implications of its decline. Besides highlighting the importance of professional initiatives shaping cancer activism, contextualizing the rise and fall of the LAC calls attention to the effects that hospitalization of cancer treatment had on aspects of cancer care that were not directly treatment-related, such as public outreach.